Effect of fire needle for ganglion cysts: A protocol of systematic review and meta-analysis of randomized controlled trials. Issue 41 (9th October 2020) - Chen, Jun; Liu, Qifang; Xiong, Jun; Lu, Lunbin; Zhu, Siyuan; Zhong, Zhiying; Tang, Genhua; Zhou, Xingchen; Guo, Han; Chen, Zhijun
Abstract: Background: Ganglion cysts (GCs) are tumor-like lesions that often occur in the soft tissues, which are mostly caused by the degeneration of mucin produced by the joint capsule and tendon sheath on the carpal dorsal joints of extremities. GCs may appear asymptomatic as benign tumors, but some patients also seek treatment because of the pain caused by these fluid-filled cysts. As a kind of complementary and alternative therapy, there have been some studies published in China which have proved that the fire needle has a better therapeutic effect on ganglion cyst. The purpose of this systematic review is to evaluate the efficacy of fire needle in the treatment of GCs. Methods: PubMed, EMBASE, the Cochrane Library, Chinese National Knowledge Infrastructure, Chinese VIP Information, Wanfang Database, and Chinese Biomedical Literature Database were searched by 2 reviewers from the inception until August 2020. The original study that randomised control trials of fire needle for GCs will be selected and is not limited by country or language. In addition, researches in progress, the reference lists and the citation lists of identified publications will be retrieved similarly. Study selection, data extraction, and assessment of the quality will be performed independently by 2 reviewers who have been trained prior to data extraction. A meta-analysis will be conduct if the quantity and quality of the original studies included are satisfactory; otherwise, a descriptive analysis will be conducted. Review Manager V5.4: (The Nordic Cochrane Centre, The Cochrane Collaboration, Copenhagen, Denmark) software will be using for data synthesis and assessment the risk of bias according by Cochrane Handbook. Result: This study will provide a comprehensive review of current evidence for the treatment of fire needle on GCs. Conclusion: The conclusion of this study will provide a judging basis that whether the treatment of GCs with fire needle is effective. INPLASY registration number: INPLASY202080032